Making the new world their own : Chinese encounters with Jesuit science in the age of discovery - Zhang, Qiong, 1964- (History of science and medicine library. Scientific and learned cultures and their institutions, 2015)
"In Making the New World Their Own, Qiong Zhang offers a systematic study of how Chinese scholars in the late Ming and early Qing came to understand that the Earth is shaped as a globe. This notion arose from their encounters with Matteo Ricci, Giulio Aleni and other Jesuits. These encounters formed a fascinating chapter in the early modern global integration of space. It unfolded as a series of mutually constitutive and competing scholarly discourses that reverberated in fields from cosmology, cartography and world geography to classical studies. Zhang demonstrates how scholars such as Xiong Mingyu, Fang Yizhi, Jie Xuan, Gu Yanwu, and Hu Wei appropriated Jesuit ideas to rediscover China's place in the world and reconstitute their classical tradition"--Provided by publisher